Causes of death and life span in Finnish gelsolin amyloidosis. (3rd July 2016) - Schmidt, Eeva-Kaisa; Atula, Sari; Tanskanen, Maarit; Nikoskinen, Tuuli; Notkola, Irma-Leena; Kiuru-Enari, Sari
Abstract: Background: Finnish type of hereditary gelsolin amyloidosis (AGel amyloidosis) is an autosomal dominant disorder. Until recently, there has only been little knowledge of fatal complications of the disease and its possible impact on the patients' life span. Methods: We identified 272 deceased patients based on patient interviews and genealogical data. After collecting their death certificates, we recorded the patients' underlying and immediate causes of death (CoD) and life span and compared them to the general Finnish population. We then calculated proportional mortality ratios (PMR), standardised for age and sex, for the CoDs. Results: The underlying CoD in 20% of the patients was AGel amyloidosis (PMR = 114.2; 95% CI: 85.6–149.4). The frequency of fatal cancers (10%) was significantly diminished (PMR = 0.47; 95% CI: 0.31–0.69). Renal complications were overrepresented as the immediate CoD in female patients (PMR = 2.82 95% CI: 1.13–5.81). The mean life span for male patients was 73.9 years (95% CI: 72.0–75.6) and 78.0 years for female patients (95% CI: 76.4–79.5) compared to 72.1 and 80.1 years for the general population. Conclusions: Our results suggest that the disease increases the risk of fatal renal complications but does not substantially shorten the life span, possibly due to the significantly lower frequency of fatal cancers. Key Messages: AGel amyloidosis may increase the risk of renal complications, especially among female patients. The frequency of fatal cancers is significantly lower. The patients' life span is comparable to that of the general population.